Investigative Journalism: Challenges and Prospects - Aryal, Deb Raj (THE ACADEMIA, 2026)
Investigative journalism serves as a vital pillar of democratic societies, functioning as a watchdog to expose corruption, abuse of power, and societal injustices. This theoretical research article explores the challenges and prospects of investigative journalism in the contemporary media landscape, drawing on social responsibility theory and watchdog frameworks to analyze its role. Key challenges include financial constraints, political interference, digital disruptions, and safety risks for journalists, which threaten the sustainability of in-depth reporting. Despite these obstacles, prospects emerge through global collaborations, nonprofit models, technological innovations like data journalism, and increased philanthropic support. By synthesizing scholarly literature and empirical insights, this article argues that while investigative journalism faces existential threats in an era of declining traditional media revenues and rising authoritarianism, adaptive strategies such as cross-border networks and multimedia formats offer pathways for resilience and enhanced impact. The analysis underscores the need for policy reforms to bolster press freedoms and funding, ensuring journalism's continued contribution to transparency and accountability. Theoretical implications highlight the evolution of journalism's epistemic and representative functions, urging a reevaluation of ethical boundaries in digital contexts.